Indel Group in Genomes (IGG) Molecular Genetic Markers . Issue 1 (19th July 2016) - Toal, Ted W.; Burkart-Waco, Diana; Howell, Tyson; Ron, Mily; Kuppu, Sundaram; Britt, Anne; Chetelat, Roger; Brady, Siobhan M.
Abstract : Genome-wide molecular markers are produced by a bioinformatics pipeline that analyzes pairs of genomic sequences to find primer pairs that amplify indel-containing regions having a targeted amplicon size and size difference. Abstract: Genetic markers are essential when developing or working with genetically variable populations. Indel Group in Genomes (IGG ) markers are primer pairs that amplify single-locus sequences that differ in size for two or more alleles. They are attractive for their ease of use for rapid genotyping and their codominant nature. Here, we describe a heuristic algorithm that uses a k-mer-based approach to search two or more genome sequences to locate polymorphic regions suitable for designing candidate IGG marker primers. As input to the IGG pipeline software, the user provides genome sequences and the desired amplicon sizes and size differences. Primer sequences flanking polymorphic insertions/deletions are produced as output. IGG marker files for three sets of genomes, Solanum lycopersicum/Solanum pennellii, Arabidopsis ( Arabidopsis thaliana ) Columbia-0/Landsberg erecta -0 accessions, and S. lycopersicum/S. pennellii/Solanum tuberosum (three-way polymorphic) are included.